Analysis of morphine, morphine-3-glucuronide, morphine-6-glucuronide, codeine and codeine-6-glucuronide using HPLC - Almoterie, Abdullataif Aaied; Alshugeer, Mohammad Suliman; Binbaz, Abdulmajeed Saad; Alangari, Waleed Abdulaziz; Alsakran, Sultan Hamdan; Almutairi, Turki Ayidh; Alblaihi, Ahmed Abdulaziz; Alenzi, Mohammed Mosier (Journal of medical and pharmaceutical sciences, 2020)
In interpretive forensic and clinical toxicology, there is a great need for the identification and detection of opiate drugs and their various glucuronide metabolites. Glucuronides are usually determined by cleavage of the glucuronide bond with an enzyme (e.g., β-glucuronidase) or acid hydrolysis to yield the parent compound, which is subsequently detected. For Gas chromatography-mass spectrometry (GC-MS) analysis this may be via derivatization to a more volatile or stable form. Direct detection of the glucuronide conjugates overcomes the critical limitations of these approaches. In this conduct, a rapid and selective reversed-phase high-performance liquid chromatographic (HPLC) assay with gradient elution and ultraviolet detection for morphine, morphine-3-glucuronide, morphine-6-glucuronide, codeine, codeine-6-glucuronide and hydrocodone was developed. The separation was performed on a gemini C18 (Octadecyl carbon chain) analytical column (150  2.0 mm, 5 µm) and detected by an ultraviolet (UV) detector at 210 nm. The mobile phase consisted of an acetonitrile–phosphate buffer (0.0125 M, pH 7.5) with elution in the gradient mode ranging from 7.5–60% acetonitrile over 25 minutes (min) with a 0.2 mL/min flow rate. The calibration curves were linear (R2 range 0.997–0.999) in the concentration range 0.025–2 µg/mL for all analytes, using hydrocodone as the internal standard. Therefore, this conduct aims to develop an efficient method of separation of morphine, codeine and glucuronides by HPLC-UV and to evaluate the use of SPME LC tips for the extraction of morphine, codeine and glucuronides from urine samples.